Microeconomics with spreadsheets - Basov, Suren (World Scientific Publishing Co. Pte. Ltd., 2017)
Microeconomics with Spreadsheets starts with the mathematical preliminaries and covers consumer theory, producer theory, general equilibrium, game theory, market structure and economics of information--Provided by publisher.